Tax and credit aids to industrial development in Southern Italy - G. ACKLEY; L. DINI (PSL Quarterly Review, 2014)
The large population and the limited resources of soil and climate appear to make industrialisation a necessary ingredient of any true solution to Italy’s “Southern problem”. Whether correct or not, this conclusion is embodied in Italian economic policy. The purpose of the present article is not to evaluate the whole program for industrialisation, but rather only one small part of it, the special aids in the fields of taxation and credit which attempt to provide rather specific additional profit incentives in favour of Southern as opposed to Northern industrial investment. After a brief description of these provisions, and a general analysis of their effects, the authors attempt, through a series of hypothetical but realistic examples, to assess their quantitative importance and to understand to what extent they affect the profit margins on potential Southern investment.